2011
DOI: 10.1007/s00213-011-2422-1
|View full text |Cite
|
Sign up to set email alerts
|

Alpha7-nicotinic receptors modulate nicotine-induced reinforcement and extracellular dopamine outflow in the mesolimbic system in mice

Abstract: The present results reveal new insights for the role of α7 nAChRs in modulating the action of nicotine within the mesolimbic circuit. These receptors appear to potentiate the reinforcing action of nicotine administered into the VTA while regulating its action over time on DA outflow in the ACb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 70 publications
(93 reference statements)
0
48
0
Order By: Relevance
“…Nicotine binds with high affinity to aBTX-insensitive receptors, which are always heteromeric. Heteromeric a4b2-and homomeric a7-containing receptors are the most widespread nAChRs in the brain [34,35], and they are involved in the reinforcing effect of nicotine [36][37][38][39].…”
Section: Diversity Of Nachrsmentioning
confidence: 99%
“…Nicotine binds with high affinity to aBTX-insensitive receptors, which are always heteromeric. Heteromeric a4b2-and homomeric a7-containing receptors are the most widespread nAChRs in the brain [34,35], and they are involved in the reinforcing effect of nicotine [36][37][38][39].…”
Section: Diversity Of Nachrsmentioning
confidence: 99%
“…Local infusion of a highly selective α7 antagonist peptide, α-conotoxin ArIB [V11L, V16D], into the NAc or ACC resulted in a nearly 3 fold increase in active lever pressing and breakpoints during a progressive ratio schedule of reinforcement suggesting that a loss of α7 nAChR function in these brain areas, such as that seen with schizophrenia, increases nicotine self-administration [105]. Nicotine-associated dopamine release is elevated in α7KO mice [110] which show leftward shifts in nicotine CPP [106] following systemic nicotine injection. By contrast, α7KO mice showed impaired oral nicotine self-administration during a 2 bottle choice but only after 40 days of exposure suggesting that α7 nAChRs may differentially regulate initiation and maintenance of nicotine self-administration in α7KO mice [83, 111].…”
Section: Nachr Contributions To Addiction Phenotype: Animal Modelsmentioning
confidence: 99%
“…Indeed, we have previously shown that the VTA-hippocampus loop is specifically active late after learning and, through a process involving the D1/D5 dopamine receptordependent increase of BDNF expression in the CA1 region of the dorsal hippocampus, determines LTM duration (Rossato et al 2009). Therefore, since nicotine modulates VTA function (Wooltorton et al 2003) and cholinergic inputs to the VTA have excitatory influence on mesolimbic dopamine neurons (Good and Lupica 2009;Yang et al 2009;Zhao-Shea et al 2011), contributing to signal behaviorally relevant events as well as the rewarding properties of stimuli Chen et al 2006;Ikemoto 2007;Besson et al 2012), we investigated the involvement of nAChRs on fear memory persistence. To that end, we utilized the step-down inhibitory avoidance (IA) learning task and 3-mo-old male Wistar rats.…”
mentioning
confidence: 99%